On the Minimum and Maximum Variable Cost of Heating of the Flat in Multifamily Building - Tomasz Cholewa; Alicja Siuta-Olcha; Anna Życzyńska; Aleksandra Specjał; Paweł Michnikowski (Energies, 2023)
Heat cost allocation is commonly used in existing buildings supplied by centralized sources of heating/cooling and provided with individual metering systems. However, this process is not always fair for the users, since “fairness” strongly depends on the methods established to allocate variable and fixed costs among the dwellings. That is why unrealistic cost for heating may be allocated for specific flats. However, there is a lack of evidence about procedures as to how maximum and minimum variable cost of heating may be calculated for specific flats in multifamily building for a specific heating season. This paper presents different methods for estimation of maximum and minimum variable cost of heating of flat in multifamily buildings, the use of which depends of the availability of input data for specific buildings. Evaluation of the proposed methods is made on the example of a case study multifamily building located in Poland. It was shown that the maximum variable costs of heat purchase for specific flats in the analyzed building were in the range from 169% to 256% of the average unit cost of heat, depending on the method used. The recommendation about the accuracy of proposed methods is also provided by the authors.